Evoke - Developing Skills in Youth to Solve the World’s Most Complex Problems : Randomized Impact Evaluation Findings - Freeman, Barbara (World Bank, Washington, DC, 2018)
This paper presents the findings of an impact evaluation designed to study an educational initiative called Evoke: Youth as Agents of Change in the Colombian Peace Process. Evoke is a project-based learning model that uses storytelling, game mechanics, and global social networks, to imbue young people with the skills they need to develop social innovations that address grand challenges (e.g., refugees, poverty, climate change) in their communities. Creating novel solutions to these complex and intractable problems requires curiosity, creativity, collaboration, aggregative thinking, empathy, plus a host of other 21st century and socioemotional skills. The development of each skill individually is important but these skills are deeply intertwined and even more relevant when combined in a project-based framework.  These transferable skills enable young people to see, listen, question, imagine, think, care, act, and reflect, in a fundamentally different and potentially transformative way.